2011
DOI: 10.25225/fozo.v60.i4.a14.2011
|View full text |Cite
|
Sign up to set email alerts
|

Morphological comparison of early stages of two Japanese species of eight-barbel loaches: Lefua echigonia and Lefua sp. (Nemacheilidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“… * L. costata and L. echigonia in newly hatched larvae : total length; L. echigonia and L. torrentis : body length. 1) Present study, 2) Aoyama & Doi (2011) with CC-BY. …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“… * L. costata and L. echigonia in newly hatched larvae : total length; L. echigonia and L. torrentis : body length. 1) Present study, 2) Aoyama & Doi (2011) with CC-BY. …”
Section: Discussionmentioning
confidence: 87%
“… * Total length of L. echigonia 1) Present study 2) Uchida (1939) 3) Aoyama & Doi (2011) TL. total length; BL, body length.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2. Some studies showed embryological differences in Lefua loaches [9] [10] [11] [12]. However, we cannot perform comparative embryology among the above six species and among intraspecific populations of each species, because those studies have been done using only limited samples of two species, Lefua sp.…”
Section: In the Red List Issued By The Japanese Ministry Of The Envirmentioning
confidence: 99%